Compassionate Goddess and Filial Monk: The Influence of Confucian Values on Chinese Buddhism and Its Practices in Indonesia - Jesada Buaban (Antropologi Indonesia, 2021)
This article examines interpretations of Buddhism that have been occurred to respond to Confucian values. Textual analysis and ethnography to scrutinize Chinese ritual performances in Indonesia were employed as research method. It found that in order to serve the Confucian values, Buddhism has to emphasize filial piety alongside monastic practices. It can be seen in the stories of Guanyin saved her father and Mulian saved his mother from hell. Although the origin of these stories can be traced to the Pali and Sanskrit scriptures, they had been reinterpreted and localized to convey Confucian values and Chinese tradition. In addition, these stories also claim the superior aspects of Buddhism on the ground that filial piety should be conducted not only in this very life, but also in other spirit worlds, through a certain level of meditation practice only available in the Buddhist way.